Analytic treatment of differential equations by modified homotopy perturbation method - Chowdhury, M.S.H.; Razali, Nur Isnida; Ali, Selami; Rahman, Md Mahmudur (Faculty of Engineering, International Islamic University Malaysia (IIUM), 2012)
In this paper, the modified homotopy perturbation method is applied for analytical treatment of differential equations. The modified HPM yields an analytical solution in terms of a rapidly convergent infinite power series with easily computable terms. The efficiency of the modified technique is examined by several illustrative examples. In all cases of differential equations, the modified HPM yields the exact solutions in two iterations only.